PENGARUH GAYA KEPEMIMPINAN DAN KOMPETENSI TERHADAP KINERJA KARYAWAN DENGAN DIMEDIASI VARIABEL MOTIVASI KERJA (Studi pada Karyawan PTP. Nusantara IX (Persero) Divisi Tanaman Tahunan Kebun Karet di Kebun Getas Salatiga) - Rohmad, 11.05.51.0122; Waruwu, Penunjang (Students Journal of Economic and Management, 2014)
The purpose of this study was (1) to analyze the influence of leadership style da competence on employee motivation PTP. Nusantara IX (Persero) Division of Rubber Plant in Garden Annual Garden Brittle Salatiga. (2) to analyze the influence of leadership styles on employee performance da competence PTP. Nusantara IX (Persero) Division of Rubber Plant in Garden Annual Garden Brittle Salatiga. The population in this study were all employees of PT Nusantara Plantation Crops Division IX Annual Rubber Garden in Garden Brittle Salatiga, amounting to 375 people. Determination of the number of samples obtained using as many as 79 people Slovin. Sampling technique using a random sample (simple random sampling). Test equipment in this study using multiple linear regression. The results of this study indicate that (1) the positive effect of leadership style on employee motivation. (2) Competence positive effect on employee motivation. (3) the positive effect of leadership style on employee performance. (4) Competence positive effect on employee performance. (5) Work motivation positive effect on employee performance. (6) Work motivation does not mediate the effect of leadership style on employee performance. (7) Motivation does not mediate the effect of competence on employee performance Keywords: leadership style, competence, motivation and performance of employees Â